Male and female intelligence among undergraduate students : does gender matter? - Naderi, Habibollah; Abdullah, Rohani; Tengku Abdul Hamid, Tengku Aizan (Asian Network for Scientific Information, 2008)
The study investigated the difference between gender-role identity and intelligence of students at Universities. The samples were 153 participants consisting of 48 females and 105 males` undergraduate Iranian students in Malaysia Universities. All students were given a Catell Culture Fair Intelligence Test (CCFIT). The instrument consisted two subscales, namely, intelligence (Form A) and intelligence (Form B). Each subscale had fifty items. The mean age and SD for female`s students (FS) were 22.27 and 2.62, for ages of 18 to 27 and for male`s students (MS) mean age and SD were 23.28 and 2.43, for ages of 19 to 27. The sampling method in this study was the simple randomization method. Descriptive statistics focusing on average and t-tests were used to examine differences between male and female students in this study. The CCFIT as a questioner test included 100 items about quantitative the 2 parts of Intelligence (Form A) (50 items) and intelligence (Form B) (50 items). In general, the results were not found significant between female and male students in relation to intelligence. Further research is needed to investigate whether identify factors at the university environment influence the development of female and male`s intelligence.